Associaçoes comunitárias do meio rural : Um estudo de caso no centro oeste de Minas Gerais - Toledo, Carla; Presno Amodeo, Nora Beatriz (2014)
This paper examines the association in a rural mining town in Brazil. The results belong to a master dissertationin Rural Extension on membership organizations and public policies for rural areas aiming to identify the roles performed by membership organizations, the reasons that explained their formation and their relationship with policy making for rural areas in the case studied. It is a case study, for which interviews were conducted with representatives of the organizations in order to deepen into the issues related to their historical, the roles they play and how and whether they participate in development project proposals. The results revealed anup-down process of formation of rural organizations, being created as bargaining tools for achieving collective benefits, reproducing dependency relationships
O artigo analisa o associativismo rural de um município mineiro no Brasil. Os resultados pertence ma uma pesquisa de mestrado em Extensão Rural sobre organizações associativas e políticas públicas para o meio rural com o objetivo de identificar os papéis desempenhados pelas organizações, as razões de sua formação e a relação com o processo de elaboração das políticas. Trata-se de um estudo de caso, com entrevistas aos representantes das organizações para aprofundar nos seus históricos, nas funções que realizam e como é a participação na elaboração de propostas de desenvolvimento. Os resultados revelaram uma formação verticalizada das associações, formadas como instrumento para obtenção de vantagens coletivas e reproduzindo relações de dependência.
Keywords: Community Associations; Public Policies; Dependency Relationship; Roles; Associaçoes comunitárias^lpt; Políticas públicas; Relaçao de dependência; Papéis